Congenital Cataract in a Blackbelly Lamb - Santos, Fernanda Carlini Cunha; Braga, Ramayana Menezes (Acta Scientiae Veterinariae, 2022)
Background: A cataract is an opacity of the crystalline structure that results in impaired vision. The congenital form manifests itself at birth or shortly thereafter and might also be inherited and therefore capable of passing on to descendants. Cataracts can be caused by systemic diseases, medications, toxic substances, radiation, metabolic alterations, dietary deficiencies, inflammation, traumatic injuries, age, or genetic factors. The few Blackbelly sheep herds are located in the northeast and north regions of Brazil and are considered rare, which could result in high levels of consanguinity. In this context, we report a case of congenital cataract in a Blackbelly lamb and its possible etiology. Case: A 3-month-old lamb presented with ophthalmic alterations since birth, with white and cloudy spots in both eyes and impaired vision. In the same herd, 3 elderly sheep showed similar ophthalmic alterations. The lamb was able to follow its dam, but when walking, bumped into small objects or very close to his vision field. The lamb managed to follow the herd and dodge large objects, suggesting partial vision loss. During a physical examination, both lens showed opacity and reduced corneal reflex, pupillary reflex to direct light, pupillary reflex to consensual light, and threat reflex. Ultrasonographic examination revealed that both lens presented hyperechogenicity. Hematological values were within the reference limits. In the same herd, three elderly sheep presented bilateral cataracts (2 rams and 1 ewe) in previous years, which at that time was attributed to natural aging. One ram was the lamb’s grandfather. The other ram was the father of the female, both with cataracts. Based on history, physical examination, and complementary examinations, the lamb was diagnosed with bilateral congenital cataracts with a probable hereditary condition. Discussion: Multiple factors can be related to the etiology of cataracts, and it can be difficult to establish the correct etiology. Regarding the age of onset, cataracts can be classified mainly as congenital and senile. Senile cataract is a bilateral opacification process that involves the entire lens, with slow progression and gradual loss of vision with increasing age. In adult sheep, the high proportion of eyes affected by spontaneously arising cataracts could be related to age, increased exposure to sunlight, increased genetic susceptibility, or a combination of these factors. In this case, the herd had three adult elderly sheep with cataracts previously characterized as senile. However, after reviewing the genealogy, it was found that all animals had some degree of parentage, suggesting a hereditary factor. Congenital cataracts are expressed soon after birth, resulting from the malformation of fibers in the lens, and are generally nonprogressive. The congenital form may or may not be associated with hereditary factors. Inheritance cataracts have been reported in several breeds of dogs and usually occur as an autosomal recessive trait. Blackbelly sheep are rare in Brazil, favoring consanguinity, so we believe that cataracts are inherited in this herd. To control this ophthalmic alteration, all animals with crystalline opacities were excluded from reproduction, and the herd should be monitored in future cases. Keywords: crystalline, eye, inherited, lens, ophthalmology.